Analisis pengaruh kecepatan dan lama waktu putaran alat sentrifugal terhadap viskositas susu kedelai - maulana, Faiz sahrullah; Sakti, Arya Mahendra; Sofi, Nurul Ainu; Riandadari, Dyah (Universitas Negeri Surabaya, 2026)
This study aims to analyze the effect of variations in rotational speed and centrifugation time on the viscosity and quality of soy milk. The centrifugation process was applied to accelerate the separation of liquid and solid phases (okara) in order to improve the physical quality of soy milk. The research was conducted using an experimental method with three rotational speed variations, namely 700 rpm, 900 rpm, and 1100 rpm, and three centrifugation time variations of 15 minutes, 20 minutes, and 25 minutes. The observed parameter was the viscosity value of soy milk. The results showed that increasing rotational speed and centrifugation time significantly affected changes in viscosity. The lowest viscosity value was obtained at a rotational speed of 700 rpm, amounting to 14,531 cP, while the highest viscosity value was recorded at 1100 rpm, reaching 44,194 cP. The rotational speed of 900 rpm was considered the most optimal condition because it produced a balance in viscosity without causing excessive thickening. This study is expected to serve as a reference for determining optimal centrifugation operating parameters in soy milk processing, particularly for small- and medium-scale applications.